Influence of Gender and Reproductive Factors on Liver Fibrosis in Patients With Chronic Hepatitis B Infection. Issue 10 (October 2019) - Xiong, Ming; Li, Junying; Yang, Shuling; Zeng, Fansen; Ji, Yali; Liu, Jiang; Wu, Qiaoping; He, Qingjun; Jiang, Ronglong; Zhou, Fuyuan; Wen, Weiqun; Chen, Jinjun; et al.
Abstract : INTRODUCTION: The role of reproductive factors in the development of chronic hepatitis B (CHB) remains unknown. We assessed the potential contributions of gender, menopausal status, and menarche age to liver fibrosis in CHB. METHODS: A cross-sectional prospective study included 716 women and 716 age-matched men with CHB who were not currently receiving antiviral therapy. Liver stiffness measurement using transient elastography was used to stage liver fibrosis as F0–F1 (<7.2 kPa), F ≥ 2 (7.2 kPa), F ≥ 3 (9.4 kPa), and F = 4 (12.2 kPa). Female patients were asked regarding their age at menarche and menopausal status using a questionnaire. RESULTS: Of the 716 women, 121 (16.9%) were postmenopausal, and 80 (11.2%) had advanced liver fibrosis. Multivariate logistic regression analysis showed that the postmenopausal status compared with the premenopausal status (odds ratio [OR] = 3.65–8.83; P < 0.05) and age at menarche of >14 years compared with <13 years (OR = 2.85–3.95; P < 0.05) were significantly associated with advanced fibrosis. Compared with premenopausal women, age-matched men had a higher OR for advanced fibrosis ( P < 0.05). Compared with postmenopausal women, age-matched men did not show a significant difference in the degree of liver fibrosis ( P > 0.05). Longitudinal data analysis showed that postmenopausal women (n = 31) were significantly less likely to undergo regression of liver fibrosis after antiviral treatment vs premenopausal women (n = 19) (26.3% vs 74.2%, respectively; P < 0.001). DISCUSSION: Menopause and late menarche aggravated liver fibrosis in untreated CHB, besides menopause delayed fibrosis regression under antiviral therapy. The protective effect of female gender against fibrosis was lost for postmenopausal women. TRANSLATIONAL IMPACT: It is important to consider menopausal status and age at menarche in establishing surveillance strategies among CHB females. Postmenopausal estrogen therapy may be considered for the prevention or treatment of liver fibrosis.